The Role of Social Capital in the Investment Activities of the Ukrainian Entrepreneurs in the Czech Republic - Kovály, K. P. (Ukrainian Geographical Journal, 2025)
This research presents the concept of social capital. It highlights its use in the economic performance of the Ukrainian migrant entrepreneurs in the Czech Republic from a geographical perspective, representing a novel approach to Ukrainian (and Hungarian) social geography. The main goal of the present research was to find out the role of informal and formal ethnic ties in their business and its spatial organization. In our analysis, we use the individual approach of social capital, relying on existing academic publications but adapting it to the research field, going in line with personal ties, which are closely connected with mutual trust, cooperation, contacts, and mutual aid and solidarity. We concentrate on the first generation of Ukrainian entrepreneurs, even though the whole group of Ukrainian immigrants formed the biggest minority group in the Czech Republic for years. Using the data from the settlement-level company database obtained from the Czech State Register of Companies, we could map the spatial organization of their business locations. The article’s results are based on qualitative research from in-depth semi-structured interviews with Ukrainian entrepreneurs and key actors of the Ukrainian migrant community. Using data taken from the Czech register of Ukrainian entrepreneurs, we were able to map the spatial location of their businesses. Based on our investigation, we conclude that Ukrainian entrepreneurs do not use their social capital to the available extent. A network of contacts exists among them, but their utilization for economic cooperation is rather limited, which seems to be caused by the low level of trust. Ukrainian entrepreneurs cooperate more with Czechs or other Western entrepreneurs than with their co-ethnics. According to our findings, negative experiences inherited from the culture of the USSR contribute to this, as does the current situation with high corruption and bureaucratic system in the country of origin. The other reason for the low willingness among co-ethnics for economic cooperation is the desire of Ukrainian entrepreneurs to integrate into the Czech society. Mutual solidarity, presented in private life and economic activities, does not play a significant role. It also turned out that social capital plays an indirect role in the spatial organization of Ukrainian businesses.